2005
DOI: 10.1186/bcr1353
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of transcriptional targeting strategies for carcinoma of the breast in a tissue slice model system

Abstract: Introduction In view of the limited success of available treatment modalities for metastatic breast cancer, alternative and complementary strategies need to be developed. Adenoviral vector mediated strategies for breast cancer gene therapy and virotherapy are a promising novel therapeutic platform for the treatment of breast cancer. However, the promiscuous tropism of adenoviruses (Ads) is a major concern. Employing tissue specific promoters (TSPs) to restrict transgene expression or viral replication is an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Enhanced specificity was achieved by placing the CRAd E1A gene under the transcriptional control of the tumor selective promoter CXCR4. In this regard, the CXCR4 gene promoter revealed a superior ''breast cancer-on/liver-off'' profile in a preclinical evaluation of transcriptional targeting strategies for carcinoma of the breast in a tissue slice model system [18]. Furthermore, recent evidence points to the SDF-1a-CXCR4 complex as having an important role in progression to metastasis in several tumor contexts [13,24].…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced specificity was achieved by placing the CRAd E1A gene under the transcriptional control of the tumor selective promoter CXCR4. In this regard, the CXCR4 gene promoter revealed a superior ''breast cancer-on/liver-off'' profile in a preclinical evaluation of transcriptional targeting strategies for carcinoma of the breast in a tissue slice model system [18]. Furthermore, recent evidence points to the SDF-1a-CXCR4 complex as having an important role in progression to metastasis in several tumor contexts [13,24].…”
Section: Discussionmentioning
confidence: 98%
“…It was observed that a relatively high transcriptional activity of the CXCR4 promoter exists in breast tumor cells [93,94]. Recent studies also indicate that elements which play key roles in breast malignancy regulate CXCR4 expression.…”
Section: The Roles Of Chemokines and Their Receptors In Organ Selectimentioning
confidence: 94%
“…Despite initial enthusiasm for this form of treatment, clinical trials have been disappointing [2]. Vector targeting and TSPs are being investigated to overcome nontumor cell toxicity and poor transfection efficiency that limit the effectiveness of suicide gene therapy [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, cytotoxicity has resulted from activation of HSV-TK in non-tumor cells [3][4][5]. Tumor-specific promoters (TSP) are being investigated as a strategy to improve transcriptional specificity [6].…”
Section: Introductionmentioning
confidence: 99%